Genetic variability studies in ajwain (Trachyspermum ammi L.) - R K Kakani, S Kumari, S S Meena, R K Solanki, (Journal of Spices and Aromatic Crops, 2017)
In Ajwain (Trachyspermum ammi L.) extent of variability was assessed in eighty four genotypes using augmented design. The analysis of variance indicated presence of considerable amount of variability. Genetic coefficient of variation (GCV) was high for plant height, seed yield plant-1, length of internodes, and number of secondary branches, test weight, number of umbels plant-1 and number of seeds umbel-1. High heritability and genetic advance was found for number of seed umbel-1, number of secondary branches and seed yield plant-1. Hence, in ajwain ample amount of variability exists for the important component traits like number of secondary branches, harvest index, number of seed umbel-1 and number of umbellate umbel-1 thus the scope of improving the crop by selection in the available variability is high.